Managing Diversity in Indonesia the Role of Local Elites in a Plural Society in Religion - Legowo, Martinus; Sadewo, Fransiscus Xaverius Sri; Maliki, Zainuddin (KOMUNITAS: International Journal of Indonesian Society and Culture, 2019)
Diversity is a condition that is so in new countries after the second world wars. Therefore, they develop strategies to integrate and minimize differences, from the use of repressive means to the means of hegemony. In a situation of globalization, it is not entirely successful. By taking three local communities in East Java, this study shows that local communities have different strategies from the state. Local elites develop strategies by mixing mythology, developing rules of play in public spaces to superstructure networks.